PEMILIHAN PEKERJAAN KAUM TRANSGENDER DI PEKANBARU - Angga Rizky Ananda; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This score is submitted to qualify for a Srata 1 (S1) Sociology degree. With the title "Transgender Habitus in Pekanbaru". In the reality of life in the community, it is realized that there are various communities with various backgrounds in their social life. One of them is the life of the Transgender in Pekanbaru. A person becomes transgender because of trauma. Like a man who is very disappointed with women, because he is often hurt by his heart or left in a painful way, so that men who get treatment like that cause extreme outrage towards the opposite sex. Transgender people in choosing their jobs have several reasons behind it. Among other things: education, comfort, ability, freedom and wages. The problem raised in this study is how is the life of Transgender people in Pekanbaru? How do Transgender people choose jobs? The research method used is a qualitative research method. Research location in Pekanbaru. The informants in this study were Transgender people consisting of 7 people. 2 people work as commercial sex workers. 2 people work as a massage plus-plus. 1 person works as a salon worker. 1 person works as a salesman. Data collection techniques used were direct interviews and documentation. The results of the research are generally carried out, the writer can state that the life of the informant changes after becoming a Transgender. Where they often get rejection from the surrounding environment. Keywords : life, work, Transgender.